2015
DOI: 10.1088/1674-1056/24/6/060509
|View full text |Cite
|
Sign up to set email alerts
|

An efficient three-party password-based key agreement protocol using extended chaotic maps

Abstract: Three-party password-based key agreement protocols allow two users to authenticate each other via a public channel and establish a session key with the aid of a trusted server. Recently, Farash et al. [Farash M S, Attari M A 2014 "An efficient and provably secure three-party password-based authenticated key exchange protocol based on Chebyshev chaotic maps", Nonlinear Dynamics 77(7): 399-411] proposed a three-party key agreement protocol by using the extended chaotic maps. They claimed that their protocol coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is worth noting with the excitement that there has been a great deal of research on complexity science by the Chinese physical community, including works on stochastic resonance, bifurcations, and chaos. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Mathematically, multifractals are characterized by many or infinitely many power-law relations. In this paper, we work with a specific type of multifractal, called the random multiplicative process model, to analyze the color value and the clarity degree.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting with the excitement that there has been a great deal of research on complexity science by the Chinese physical community, including works on stochastic resonance, bifurcations, and chaos. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Mathematically, multifractals are characterized by many or infinitely many power-law relations. In this paper, we work with a specific type of multifractal, called the random multiplicative process model, to analyze the color value and the clarity degree.…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate the shortages of using a server public key and smart card, Farash and Attari [25] proposed a first chaotic-maps-based 3PAKE protocol without using a server public key, nor smart card nor symmetric cryptosystems in 2014, but Xie et al [26] demonstrated that their protocol cannot resist impersonation attack nor offline password guessing attack, and then they proposed an improved chaotic-maps-based 3PAKE protocol with the same advantages to overcome the weaknesses of Farash and Attari's protocol. In 2015, Shu [27] also showed that Farash and Attari's scheme is vulnerable to off-line password guessing attack and suffers communication burden, and proposed an improved one.…”
Section: Introductionmentioning
confidence: 99%